BANTINGAN MOROTE SIO-NAGE DITINJAU DARI POSTUR TUBUH - Bayu Nugraha Murdiansyah (CV. Multi Kreasi Media, 2022)
In ju-jitsu martial arts, there are techniques for slamming, hitting, kicking and locking and these various techniques are widely used in matches starting from these various techniques, the researcher wants to see the slamming technique, namely how the right leg position is to do a slamming moote seo- nage in terms of posture, research